Toward a Cosmopolitan Ethics of Mobility The Migrant's-Eye View of the World - Sager, Alex (Mobility & Politics, 2018)
This book proposes a cosmopolitan ethics that calls for analyzing how economic and political structures limit opportunities for different groups, distinguished by gender, race, and class. The author explores the implications of criticisms from the social sciences of Eurocentrism and of methodological nationalism for normative theories of mobility. These criticisms lend support to a cosmopolitan social science that rejects a principled distinction between international mobility and mobility within states and cities. This work has interdisciplinary appeal, integrating the social sciences, political philosophy, and political theory. Alexander Sager is Associate Professor of Philosophy at Portland State University, USA.